2021
DOI: 10.1007/s13318-021-00723-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cytochrome P450 3A4 Induction and Inhibition on the Pharmacokinetics of BI 425809, a Novel Glycine Transporter 1 Inhibitor

Abstract: Background and ObjectiveIncreased glycine availability at the synaptic cleft may enhance N-methyl-D-aspartate receptor signalling and provide a promising therapeutic strategy for cognitive impairment associated with schizophrenia. These studies aimed to assess the pharmacokinetics of BI 425809, a potent glycine-transporter-1 inhibitor, when co-administered with a strong cytochrome P450 3A4 (CYP3A4) inhibitor (itraconazole) and inducer (rifampicin). Methods In vitro studies using recombinant CYPs, human liver m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Another reason for reduced absolute bioavailability following a single oral dose of BI 425809 25 mg in a tablet form may be elimination via the enzyme CYP3A4 upon first-pass metabolism [ 11 ]. The major metabolic pathway for BI 425809 is mediated by CYP3A4, which is the most highly expressed CYP isoform in the liver and intestines, and is important in determining the exposure of oral medications [ 16 , 17 ]. In the present study, AUC 0–∞,norm was lower after oral dosing versus IV infusion, as was gMean C max , norm , which was around 80% lower following oral administration of BI 425809 versus IV dosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for reduced absolute bioavailability following a single oral dose of BI 425809 25 mg in a tablet form may be elimination via the enzyme CYP3A4 upon first-pass metabolism [ 11 ]. The major metabolic pathway for BI 425809 is mediated by CYP3A4, which is the most highly expressed CYP isoform in the liver and intestines, and is important in determining the exposure of oral medications [ 16 , 17 ]. In the present study, AUC 0–∞,norm was lower after oral dosing versus IV infusion, as was gMean C max , norm , which was around 80% lower following oral administration of BI 425809 versus IV dosing.…”
Section: Discussionmentioning
confidence: 99%
“…These observations could likely be first-pass metabolism via gastrointestinal and hepatic CYP3A4, which would only affect the oral dosing route. In a previous study, the pharmacokinetic interaction of multiple oral doses of the CYP3A4 inhibitor itraconazole and BI 425809 was assessed [ 18 ]. It was observed that there was a small increase in C max (gMean ratio 116.1% (90% CI 108.0–124.7)) following co-administration of BI 425809 and itraconazole, which most likely reflected the blocking of CYP3A4 in the first-pass metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The study investigated the effects of 2 mg, 5 mg, 10 mg, or 25 mg BI 425809 administered daily for 12 weeks, as an add-on strategy to antipsychotic monotherapy and cotreatment with a second antipsychotic [ 358 ]. BI 425809 was well tolerated in healthy volunteers as well as in patients [ 358 , 385 ]. A randomized trial combining BI 425809 with computerized cognitive training has been recently planned in order to consolidate the results obtained on cognitive functions [ 384 ].…”
Section: Other Modulators Of the Glycine B Site At Nmdarmentioning
confidence: 99%
“…Twenty metabolites of BI 425809 were identified in male human plasma, urine, and feces. [19][20][21] The structures of 11 of these metabolites were unequivocally determined. Among them are the major metabolites BI 761036 (6) and BI 758790 (9) shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%